(untitled) - Blaker, Michael (New York, 1977)
This is a solid piece of scholarly research. The author's special perspective and analytical method break new ground in the study of Japan's foreign relations.
Keywords: Japan,Japan; Foreign relations,Foreign relations; 1868-1912,1912-1945